Hyperkyphosis and back pain are not associated with prevalent vertebral fractures in women with osteoporosis. (March 2015) - Ribom, Eva L.; Kindmark, Andreas; Ljunggren, Östen
Abstract Vertebral fractures (VFs) are the clinical consequence of spinal osteoporosis and may be associated with back pain and aggravated kyphosis. However, the relative importance of VFs as an underlying cause of kyphosis and chronic back pain is not known. The aim of this study was to investigate the relationship between prevalent VFs and the size of kyphosis, and back pain in osteoporotic women. Thirty-six women, aged 74.6 ± 8.3 years, were consecutively recruited from the osteoporosis unit at Uppsala University Hospital. The patients had 1–9 radiographic verified VFs. Tragus wall distance (TWD) and numeric rating scale were used to measure kyphosis and pain. All patients had a hyperkyphosis (TWD ≥ 10 cm). Notably, there were no associations between numbers or location of VFs versus size of kyphosis (ρ = 0.15, p = 0.4; ρ = −0.27, p = 0.12) or severity of back pain (ρ = −0.08, p = 0.66; ρ = 0.16, p = 0.35). Furthermore, no association was evident between kyphosis and back pain (ρ = −0.02, p = 0.89). There was, however, an association between size of kyphosis and age (R = 0.44, p = 0.008). In conclusion, these data suggest that prevalent VFs are not significantly associated with kyphosis or chronic back pain, in patients with manifest spinal osteoporosis.